THE LEARNING MANAGEMENT USING PROBLEM BASE LEARNING WITH TEAM GAME TOURNAMENT TECHNIQUE ON MATHEMATICAL PROBLEM SOLVING ABILITY OF GRADE 11 STUDENTS - Nukkhong, Patihan; Cheausuwantavee, Chommanad; Yamrung, Rungtiwa (Journal of MCU Nakhondhat, 2024)
The purpose of this study were 1) To compare mathematical problem-solving ability of grade 11 students before and after using Problem–Based Learning with Team Game Tournament technique 2) To compare mathematical problem-solving ability of grade 11 students after using Problem–Based Learning with Team Game Tournament technique to the criterion of 70%. The experimental method is Quasi-Experimental Research by One Group Pretest–Posttest Design. The sample of this study included 30 of eleventh gradestudents studying in the second semester of 2023 academic year at Srinakharinwirot University Prasarnmit Demonstration School (Secondary). They were selected by using the cluster random sampling technique and using the classroom as the unit of randomization. The duration of the research was 12 periods. The instruments used in this study were lesson plans and mathematical problem-solving ability test. The statistics procedures used for data analysis were mean, standard deviation, t-test for dependent samples and t-test for one samples. The results showed that 1) The mathematical problem-solving ability of grade 11 students after was higher than before using Problem–based learning with Team Game Tournament Technique at a statistically significant level of .05, 2) The mathematical problem-solving ability of grade 11 students was higher than the criterion of 70% after using Problem-based learning with Team Game Tournament Technique with a statistically significant level of .05.